Effectiveness and Legal Protection in Health Services in Public Hospitals For BPJS Health Participants Sembiring Deli Tua Public Hospital Study - Sembiring, Alprindo; Satria, Beni; Sidi, Redyanto (Journal of General Education Science, 2023)
As a form of appreciation for the aspirations of the Indonesian people in achieving social welfare, health services are very crucial. Pancasila and the 1945 Constitution, as the foundation of the state, set guidelines for state implementation, including in the health sector. To realize the National Social Security System (SJSN), especially National Health Insurance (JKN), BPJS was initiated. However, there are many obstacles encountered in the health services sector, especially those related to legal aspects for BPJS Health members who receive treatment in hospitals. This study aims to research and find a way out of this problem. First of all, this study will review the implementation of rights and responsibilities between hospitals and patients based on Law no. 44 of 2009. Next, an assessment of the effectiveness of the implementation of Law no. 36 of 2009 concerning Health and Law no. 24 of 2011 concerning BPJS, especially in providing excellent and equal health services for BPJS Health members in state hospitals. Finally, this study will find elements that hinder the optimization of health services for BPJS members and their impact on the implementation of BPJS at RSU Sembiring using a Normative Juridical research approach. The research results show that the rights and responsibilities between hospitals and patients, including BPJS Health members, have been clearly defined in various regulations and laws in Indonesia. Regular patients and BPJS members have equal rights in obtaining access to quality and safe health services. However, BPJS members are required to pay contributions and follow a predetermined referral system. RSU Sembiring Deli Tua functions in accordance with existing provisions, including the health service referral system. In July, Sembiring RSU successfully served 8318 BPJS patients, indicating its effective service. However, there are still obstacles on the ground that require attention from policymakers. Overall, RSU Sembiring has been successful in providing services to BPJS Health members in an efficient manner and in accordance with the law. RSU Sembiring is a model for how health institutions need to adapt and collaborate with BPJS and the government to face and find solutions to the obstacles they encounter, so that effective health services and legal protection for BPJS members are guaranteed.